Wavelength scaling of high harmonic generation for 267 nm, 400 nm and 800 nm driving laser pulses. (1st September 2017) - Marceau, C; Hammond, T J; Naumov, A Yu; Corkum, P B; Villeneuve, D M
Abstract: We convert optical frequencies to the extreme ultraviolet (XUV) via high harmonic generation. We compare the high harmonic conversion efficiency from three different driving wavelengths of 267, 400 and 800 nm, finding that the efficiency scales as λ − 2.9 where λ is the driving laser wavelength. We find that the higher conversion efficiency and the increased free spectral range between harmonic orders are benefits of a shorter driving wavelength as an XUV source. We use these XUV sources to measure the photoelectron spectra of several atomic and molecular species.